The Effectiveness of Self-Healing Approach on Cognitive Distortions and Interpersonal Forgiveness among Women with Psychological Distress - Nasresfahani, Maliheh; Hayati, Mozhgan; Latifi, Zohreh (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The purpose of this study was to determine the effectiveness of self-healing approach on cognitive distortions and interpersonal forgiveness among women with psychological distress. Methods: This research was a semi-tested study with pre-test, post-test and follow-up of control group, which was carried out on women who chose educational counseling center in region no 2, of Isfahan city in the second half of 1399. After screening by using Kessler’s psychological distress questionnaire (2002), 40 women were selected and placed randomly in two experimental and control groups (each group of 20 females). The research tools of cognitive distortions belonged to Hamamchi and Boyuk (2004) and interpersonal forgiveness tool belonged to Ehteshamzadeh (2010). The experimental group received 14 sessions of 90-minute training of Lloyd and Johnson (2014) self- healing method, and the control group did not receive any training and interference. Data were analyzed using frequent measurement variance test in SPSS software version 25. Results: The results of this study showed that self-healing approach on cognitive distortions (f = 3.20, p=0.05) and forgiveness (F = 11.14, P = 0.01) of women with psychological distress was effective in post-test phase and the effects of intervention over time remained constant (p <0.001). Conclusion: It is recommended to pay more attention to education in families due to its effectiveness in improving the psychological health of women with psychological distress, as well as increasing the forgiveness and reducing the cognitive distortions and it may be employed as an effective educational method for improving the lifestyle and mental health of the women with psychological distress.